Объяснение:
1) 99 : 99 +9= 10
2) 9 : 9 + 9+ 9- 9= 10
3) 9- 9+ 9+ 9 : 9= 10
4) 99 : 9 - 9 : 9= 10
5) 9 * 9 : 9 : 9 +9= 10
6) 9 : 9 * 9 : 9+9 = 10
7) 9 + 9 : 9 + 9 -9=10
8) 99⁹⁻⁹ +9 =10
9) 9⁹ : 9⁹ + 9 =10
10) 9⁹ * 9⁻⁹ +9=10
11)
12)
13)
14) 9 : 9 + 9 * 9 :9= 10
Объяснение:
1) 99 : 99 +9= 10
2) 9 : 9 + 9+ 9- 9= 10
3) 9- 9+ 9+ 9 : 9= 10
4) 99 : 9 - 9 : 9= 10
5) 9 * 9 : 9 : 9 +9= 10
6) 9 : 9 * 9 : 9+9 = 10
7) 9 + 9 : 9 + 9 -9=10
8) 99⁹⁻⁹ +9 =10
9) 9⁹ : 9⁹ + 9 =10
10) 9⁹ * 9⁻⁹ +9=10
11)![9\frac{9}{9} * \frac{9}{9}= 10](/tpl/images/0925/3541/68f73.png)
12)![9 +\frac{9}{9}- 9 + 9= 10](/tpl/images/0925/3541/960a6.png)
13)![\frac{9}{9} * \frac{9}{9} +9= 10](/tpl/images/0925/3541/84519.png)
14) 9 : 9 + 9 * 9 :9= 10